The relationship between job embeddedness and voluntary turnover intentions in the context of some situational factors - an analytical study of the opinions of faculty members at the College of Administration and Economics - Al-Qadisiyah University - Amer Ali Hussein Atwi (Iraqi Journal for Administrative Sciences, 2025)
This research hypothizes that relationship between job embeddedness and voluntry turnover intensions is conditional relationship by existing number of situational factors: Work related nagitive shocks, commute time and financial requirements. Specifically, this research supposes that nagitive shocks and financial requirements influence relationship between organizational embeddedness and turnover intensions, and commute time and financial requirements influence relationship between community embeddedness and turnover intensions. The data were colleted by using questionnaire in a sample of (77) of faculty in College of Administrative and Economic- of AL-Qadisiya University. For testing the hypotheses and achiveing the research's goals, set of statistical tools such as Cronbach alpha, simple correlation coefficient and hierarchical multiple regression analysis were used. Results indicate that job embeddedness negatively related with turnover intensions. In addition to, the results indicate that situational factors (nagitive shocks, commute time and financial requirements) have role in influencing relationship between job embeddedness and turnover intensions. In lights of these results, set of conclusions and recommendation were formulated. One of these recommendations was reducing exposure to negative shocks by building " Employee Voice System".